Karakteristik Efikasi Diri Pembuatan Keputusan Karir Pada Remaja - Aslama Puji Astuti (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
Career confusion can inhibit confidence in determining the goals of future plans. Information on the characteristics of self-efficacy career decision making is needed as an effort to develop one's behavior and skills. Self-efficacy is the individual's trust in his ability to do something. The process of identifying previous journals through searches in the last 16 years (2000-2017) through electronic media, books, Google Scholar, Elsevier, and Sage. The results showed the characteristics of self-efficacy career decision making in adolescents were self-assessment, job information, goal selection, planning, and problem solving. The results of this study could be one of the references of knowledge for students, teachers, and parents in making career decisions in adolescents.